Application of the Nano-Drug Delivery System in Treatment of Cardiovascular Diseases - Deng, Yudi; Zhang, Xudong; Shen, Haibin; He, Qiangnan; Wu, Zijian; Liao, Wenzhen; Yuan, Miaomiao (Frontiers in Bioengineering and Biotechnology, 2020)
Cardiovascular diseases (CVDs) have become serious threat to human life and health. Though many drugs acting via different mechanism of action are available in the market as conventional formulations for the treatment of CVDs, they are still far from satisfactory due to poor water solubility, low biological efficacy, non-targeting and drug resistance. Nano-drug delivery systems (NDDSs) provide a new drug delivery method for the treatment of CVDs with the development of nanotechnology, demonstrating great advantages in solving the above problems. Nevertheless, there are some problems about NDDSs need to be addressed, such as cytotoxicity. In this review, the types and targeting strategies of NDDSs were summarized, and the new research progress in the diagnosis and therapy of CVDs in recent years was reviewed. Future prospective for nano-carriers in drug delivery for CVDs includes gene therapy, in order to provide more ideas for the improvement of cardiovascular drugs. In addition, its safety was also discussed in the review.